Enraizamento de estacas de Caesalpinia echinata Lam. Em hidroponia - Valeri, Sérgio Valiengo [UNESP]; de Sá, Ariadne Felício Lopo [UNESP]; Martins, Antonio Baldo Geraldo [UNESP]; Barbosa, José Carlos [UNESP] (My University, 2012)
This study aimed to determine the indole-3-butyric acid (IBA) requirement and proper concentration for Caesalpinia echinata rooting in a hydroponic system for plantlet production. The experiment was conducted in a greenhouse of the 'Faculdade de Ciências Agrárias e Veterinárias', UNESP, in Jaboticabal, São Paulo state. The vegetal material consisted of 160 stem cuttings that were 11 to 12 cm in length with two pairs of leaves, prepared from young seedlings. The cutting bases were treated by slow immersion in 5% ethanol solution containing 0, 100, 200 and 400 mg L-1 of IBA during 14 hours and by fast immersion in 50% ethanol solution containing 0, 1000, 3000 and 5000 mg L-1 of IBA during 5 seconds. The cuttings were maintained in the hydroponic system for 90 days and, for additional 90 days in plastic bags containing substrate (Plantmax®) under intermittent mist. After 90 and 180 days of rooting, the percentage of cuttings that survived, the rooting percentage and the number and length of adventious root were evaluated. Cuttings should be treated with IBA at 100 mg L-1 for 14 hours and placed to root in a hydroponic system.
Rooting cuttings of Caesalpinia echinata Lam. In hydroponic system
Keywords: Auxin; Brazil wood; Indole-3-butyric acid; Rooting